Active Learning Using Smart Phones in a Flipped Classroom: A Case Study on Developing Final Videos in Silviculture. Issue 1 (15th June 2017) - Windmuller‐Campione, Marcella A.; Carter, David R.
Abstract : Core Ideas: The ubiquity of smart devices is changing classroom capabilities in higher education natural resource classes. The final video project extends the active learning environment outside the physical classroom into the forest. The final video assignment is essentially a cumulative, open‐book exam where students practice presentation skills and interact with technology. This assignment can be adapted for other subjects and/or larger classes by shifting the focus of the rubric to encompass the goals of the class. College students, instructors, and the population at large are increasingly connected through smart phones and tablets, shifting how we interact at a personal and professional level. Smart devices allow students to interact with data and science in novel ways; however, these devices can also be distracting and inhibit student learning. Instructors at all levels of education are beginning to develop activities that utilize smart devices to increase learning. In this case study, smart devices were utilized to create videos in an upper division silviculture class at the University of Minnesota. Students created a final video prescription for a forest stand of their choosing, incorporating knowledge gained throughout the semester. Students' videos were assessed on five major components: (1) the location and land‐use history; (2) stand composition, structure, and stage of stand development; (3) goals and objectives; (4) silvicultural systems; and (5) correct use of terms. Video editing and video quality were not included in the assessment. The final video assignment was an alternative to a final exam. The final video assignment allowed students to practice their communication skills and think creatively; skills that have been repeatedly rated as important by prospective employers in the natural resource field. The majority of students surveyed ( n = 21 of 23) responded positively to this project. This assignment can be easily modified for larger class sizes and different disciplines. Impact Statement Many students have powerful computers sitting in the palms of their hands everyday. These smart phones can and do offer many distractions but they can also be powerful teaching tools. This article demonstrates one example of how a video filmed on a smart phone can replace a final exam. These videos are a win–win: students enjoy producing the videos, and as an instructor they are more enjoyable to grade.